An investigation on Okeme practice in Lango district - Agwe, Spellman Tobias (Kampala, 1970)
Thesis (Dip. Educ.) - Makerere University College, National Institut e of Education, 1970.
Keywords: Musical instruments -- Uganda -- Lango district; Pipe music -- Case studies -- Uganda -- Lango District